116k views
2 votes
Multiple Choice Question.
Show Work Needed.

Multiple Choice Question. Show Work Needed.-example-1

1 Answer

0 votes

First of all, every number in each row is odd, so we can eliminate 392 and 394.

The number of elements in each row forms an arithmetic sequence:

• 1st row : 1 element

• 2nd row : 3 elements - and 3 - 1 = 2

• 3rd row : 5 elements - and 5 - 3 = 2

• 4th row : 7 elements - and 7 - 5 = 2

and so on, so that the
n-th row has
1 + 2(n-1) = 2n - 1 elements.

This means that in
n-1 complete rows, there is a total of


\displaystyle \sum_(i=1)^(n-1) (2i-1) = n^2 - 2n + 1

elements, so that the first element in the subsequent
n-th row is the
(n^2-2n+2)-th number in the sequence {1, 3, 5, 7, …}, i.e the
(n^2-2n+2)-th odd positive integer. To compute the sum, I use the following well-known formulas.


\displaystyle \sum_(i=1)^n 1 = n


\displaystyle \sum_(i=1)^n i = \frac{n(n+1)}2

Now, the
n-th term of the sequence {1, 3, 5, 7, …} is simply
2n-1, the
n-th odd positive integer. So the first element in the
n-th row is


2(n^2-2n+2) - 1 = 2n^2 - 4n + 3

and hence the 1st element of the 15th row is


2\cdot15^2 - 4\cdot15 + 3 = \boxed{393}

User Drobson
by
6.1k points